Constructing in Minecraft in Primary School as a Boundary-Crossing Practice - Giuseppe Ritella; Roberto Marcone (MDPI AG, 2024)
This study explores the educational adoption of Minecraft as a boundary-crossing practice in primary schools. Previous research indicates that Minecraft can facilitate connections between educational activities and students' out-of-school experiences, promoting the development of skills such as creativity, innovation, and collaboration. Using a qualitative approach, this study analyzed group interviews with 37 primary school students who participated in a Minecraft-based school project. The analysis focused on instances of boundary crossing associated with the Minecraft activity, allowing an examination of how various socio-cultural boundaries were overcome. The results suggest that educational activities in Minecraft can facilitate connections between school and out-of-school contexts. Moreover, the results indicate that Minecraft can serve as an interdisciplinary learning environment, enabling students to acquire knowledge and skills across diverse domains and disciplines. The analysis also underscores the significance of teachers' design work in transforming the game into an educational resource. Overall, this article argues that the educational adoption of Minecraft has the potential to foster the construction of continuity between students' different spheres of life, as well as prompting a reconsideration of students' previous cultural classifications and social positions.